Calculation of specific operating modes of relay protection for AC traction networks - K. S. Subkhanverdiev (Вестник Научно-исследовательского института железнодорожного транспорта)
Relay protection of traction networks against short-circuit currents in alternating current sections should have both selectivity and speed. However, in areas with an increased probability of burnout of contact wires during a short circuit, selectivity is often put away to increase the speed of response. Such operating modes of relay protection in the traction network are specific. The author considers one of these modes, namely, the operation of distance protections with an increased step area without time delay with a partially non-selective protection system, which ensures the fastest possible shutdown of damage within the entire protected area. At the same time, it is indicated that an increase in the coverage area of a step without a time delay to the size of the protected area can cause non-selective tripping of a number of switches in case of damage near substations or a sectioning post. Therefore, it is proposed to select the optimal value of the tunable zone of non-selective protection action, at which the probability of non-selective tripping of switches will be minimal. For this, the author presents an analytical solution to this problem, which allows automating calculations when forming proposals for setting up protection in a specific operating mode. It is noted that by choosing the sensitivity coefficient value in the formulas, it is possible to adjust the zone of non-selective action of distance protections so that its real value will approach the size of the protected area, while remaining strictly larger than it, which will eliminate the danger of burnout of contact wires in case of a short circuit and reduce the probability non-selective disconnection of switches on the site.